Transfer Prices Implication upon Tax System. The Romanian Experience - DUMITER, Florin; BOIÈšĂ, Marius (Journal of Legal Studies, 2017)
Transfer prices are a top field in financial and legal scientific research and practical activity. Although this research field is still in the beginning, due to its complexity, as well as it‘s inter-, multi- and transdisciplinarity, it can be noted that empirical studies, as well as practical researches in economic and legal matters, have intensified. Moreover, this field of transfer prices is in close connection with the area of international double taxation, which shows its international character. In this article we sought a holistic approach to the transfer price phenomenon, dealing with economic and legal technical aspects that we believed are important to emphasise. Without addressing the issue of transfer prices in an exhaustive manner, in this article we presented both the legal and the economic framework of transfer prices in Romania. The added value of this article lies in the approach to transfer prices, both legally and economically.